Core-Level States of Single-Electron Adsorption Complexes Ge on Si (001) (42) - Tkachuk, O.I.; Lobanov, V.V.; Terebinska, M.I. (Physics and Chemistry of Solid State, 2015)
Calculations (DFT, B3LYP, 6-31 G**) chemical shifts core-level components of germanium atoms, which are included in the surface layer of cluster Si96H84•Ge2, modeling complex molecular adsorption on germanium faces reconstructed Si(001)(4´2), showed that the magnitude of the shift depends on the relative position of atoms Ge. When introducing a single atom in a crystal germanium substrate, this shift is positive, and the introduction of two atoms leads to negative chemical shift. Given the interpretation of the results based on the charge distribution in clusters, the so-called electrostatic approximation.